Growing a plant you cannot see : ex situ propagation of the endoparasite Rafflesia speciosa to strengthen in situ conservation - Molina, Jeanmaire; Erickson, Mick; Emanuel, Isabel; Jones, Stephen; Kautz, Kirsten; Gutman, Benjamin; Pedales, Ronniel; Napulan, Macario Nicer; Muyong, Marites; Mursidawati, Sofi; Ngatari; Bumanglag, Pola Geneva; et al. (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2026)
The genus Rafflesia R.Br. ex Gray (Rafflesiaceae) produces the world’s largest flowers, yet most species are critically endangered, making the flower a symbol of global plant conservation. As a holoparasite confined to the woody vines of its sole host, Tetrastigma (Miq.) Planch. (Vitaceae), Rafflesia remains notoriously difficult to study and propagate. Its cryptic endophytic life cycle – persisting as microscopic tissue within its host for years before emergence – has long impeded ex situ conservation, such that its cultivation has aptly been described as ‘growing a plant you cannot see’. Grafting of infected host material has been the only proven method. After more than a decade of diverse attempts, we report the first viable propagation of R. speciosa Barcelona & Fernando-infected pieces sourced from the Philippines at the United States Botanic Garden in Washington, DC – the first documented cultivation of Rafflesia in the Western Hemisphere. Our approach combined two complementary methods: (1) rooting infected stem and root cuttings, and (2) grafting infected root tissues onto established Tetrastigma vines. Infection was verified using a combined molecular (PCR) and histological diagnostic framework. Notably, one graft produced two Rafflesia buds (cupule stage) approximately 2.5 years post-grafting, representing the first evidence of bud initiation outside Southeast Asia. This study (1) establishes replicable glasshouse propagation protocols for Rafflesia-infected Tetrastigma; (2) demonstrates a practical PCR-histological approach for confirming infection prior to budemergence; and (3) shows that infected tissues can preserve endophytic germplasm beyond the lifespan of the original scion. These outcomes were achieved despite the formidable logistical barriers of transcontinental permitting and transport, involving a legally protected Philippine endemic and a US-regulated organism. These methods mark a breakthrough in ex situ Rafflesia conservation, safeguarding vital germplasm and strengthening the future of in situ recovery efforts, enabling the maintenance of this cryptic parasite within its host until it emerges as one of the world’s largest flowers. This work was funded by NSF #2204938/2346626 to Jeanmaire Molina and by a cooperative grant with the US Botanic Garden.